Unleashing the power of cassava in Africa…are we there yet? - James, B.D.; Bramel-Cox, P.J.; Witte, E.R.; Asiedu, Robert; Watson, D.; Okechukwu, R.U. (International Society for Tropical Root Crops, 2012)
Cassava has long been expected to play a key role in rural economic growth in Africa, but has it happened yet? Although research partnerships have produced elite cassava varieties with 50% more yield potential and have demonstrated technologies to improve processing and increase marketing of cassava, the sub sector is constrained by low productivity and marketing difficulties. In DR Congo, Ghana, Malawi and Sierra Leone, for example, the actors in the cassava value chain are yet to respond to trade opportunities estimated in 2007 at 59 million through the replacement of imported wheat flour with locally produced high quality cassava flour. Industrial demand for cassava would also aggravate hunger and poverty if yields did not increase from current national averages of 5 to 19 t/ha to the more than 25 t/ha expected from released varieties under low input agriculture. In 2008, USAID and IITA initiated the project Unleashing the Power of Cassava in Response to Food Price Crisis (UPoCA) as a multi-country and inter-institutional partnership enabling the cassava sub sectors to realize their full potential in rural economies. The UPoCA project covers DR Congo, Ghana, Malawi, Mozambique, Nigeria, Sierra Leone, and Tanzania and draws on prior research results to increase on-farm cassava productivity and value adding processing for markets. By the end of 2009, smallholder beneficiaries associated with 55 partner organizations and 11 agriculture-related firms established 306 community for cassava stems multiplication sites and root production farms totalling 10,097 ha with 58 improved varieties. Through experiential learning at 24 hands-on short-term courses, 345 men and 142 women learnt improved techniques in cassava production, processing, product development, and packaging/labelling and eight technologies were introduced to rural communities. The evolving UPoCA achievements show that a longer-term cassava research for development partnership platform of this nature will enable the cassava subsectors to contribute significantly to rural economic growth in Africa.